Imaginal architectural devices and the ritual space of medieval necromancy. Issue 4 (December 2020) - Franchetto, Andrea
Abstract: The material and spatial dimensions documented in the manuscripts of ritual magic that circulated in the medieval and early modern periods have long eluded researchers. Studying where those rituals take place is important to understand the history of the practice of ritual magic. Few attempts have been done to interpret the reasons behind the construction of magic circles and the use of domestic locations. The author introduces a new interpretative category of such ritual spaces: imaginal architectural devices (IADs). IADs pick out a specific kind of portable, spatially unfixed ritual space, where "magical" ones are a key example. They are temporary architectural artefacts, attested across a swath of sources of ritual magic, that work as strategic tools for orienting cognition, behavior, and belief. Drawing on spatial theory and cognitive studies, the author constructs IADs as a typological category for comparative analysis. It describes architectural operations that work at the interplay between mental projections and material culture, and that modify the perception of space. In the second part of the article, IADs will be applied to study the circles described in the second section of the Liber Iuratus Honorii, a thirteenth-century handbook containing instructions on how to conjure different ranks of spirits. In the end, the author suggests future directions of research on the transmission of IADs into contemporary ritual magic.